PENINGKATAN KETERAMPILAN PEMECAHAN MASALAH MURID MENGGUNAKAN PENDEKATAN COMPUTATIONAL THINKING (CT) PADA MATERI POLA BILANGAN DI SEKOLAH DASAR - Feronika, Afrilia; Andika, Refiona; Zainil, Melva; Salmaini, Salmaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low problem-solving skills of students in learning mathematics in elementary school. Observations in class IV B at SD Negeri 08 Lubuk Layang showed that students had difficulty understanding story problems, identifying important information, and determining steps to solve them, which affected students' academic performance. To address this problem, computational thinking (CT) was used, emphasizing a systematic thinking process through decomposition, pattern recognition, and abstraction. This study aims to describe the design of the teaching module, the implementation of learning, and the improvement of students' problem-solving skills using a CT approach on the number pattern material for class IV at SD Negeri 08 Lubuk Layang. This study used classroom action research (CAR) conducted in two cycles with quantitative and qualitative approaches. The research procedures included planning, implementation, observation, and reflection. The research subjects were 14 students of class IV B. Data collection techniques use test and non-test techniques, while data analysis uses quantitative and qualitative data analysis. The research results show that students' problem-solving skills increased from an average of 71.8% in cycle I to 93.6% in cycle II. Thus, the CT approach is effective in improving students' problem- solving skills in number pattern material in elementary school.